NEW SKILLS AND ROLES FOR TEACHING AND LEARNING IN HIGHER EDUCATION IN THE CONTEXT OF THE COVID-19 PANDEMIC - Mauritti, R; João Paiva Monteiro; Belchior-Rocha, H.; Luis Carneiro; Rodrigues, M. (13th International Conference on Education and New Learning Technologies, 2021)
The pandemic and the confinement have had an impact on all aspects of our lives, in education and not least in higher education, especially on all those who are already part of the higher education communities, as students and teachers, but also on all future applicants who want to prepare and start their academic path. In this pandemic context, we are now experiencing a rapid and emerging transformation of teaching and learning processes, which is leading to new and innovative pedagogical approaches and practices for many of the teachers and students. For all those who teach, learn, research, and are employed at universities, the pandemic has set unprecedented challenges. One thing is certain, higher education as we know it will never be the same again. This setting of pedagogical, organizational, and technological change has forced those involved in the teaching and learning processes, both teachers and students, to profound changes in their work processes, their habits and behavior, their communication tools and processes, interaction, and learning evaluation methods. The aim of this paper is to identify and systematize new skills that are being required from teachers and students, and how they can acquire and develop these skills. The transformation in education is intrinsically related to the digital transformation of teaching and learning processes, which means that universities are compelled to evolve from face-to-face teaching to pedagogical approaches supported by digital tools. It will be fundamental to guarantee university communities a set of digital skills and competencies, developing digital and informational literacy, which, while maintaining the preference for face-to-face activity, can legitimize the justification for the change in the educational paradigm and can also recognize positive factors in teaching supported by digital technology. Not only the teachers, but also the students recognize the lack of suitable digital and computer skills for pedagogical processes, and they also believe that they were overwhelmed with more workload and were unable to find that the new teaching environment would allow an improved performance and higher quality of learning. These processes of pedagogical change supported by technologies are not new, but are becoming more emergent now, under the circumstances of the pandemic. In 1995, Berge identified teachers' roles in four dimensions: pedagogical, social, academic management, and technological, later on he referred to a change in roles that would focus more on informal, collaborative, reflective learning with student-generated content. The most recent research reveals a taxonomy of digital roles and competencies for teaching staff, such as planning and time management skills, technological readiness and computer literacy, as well as, enhancing teacher-student and student-student relationships, guiding student learning, improving intervention and monitoring, and driving the process of learning and learning quality assessment (learning analytics). Overall, we will address the roles and competencies of teachers and students to develop digital pedagogical processes that enable effective and meaningful learning, as opposed to a transfer of the traditional role of teacher and student to the online environment, replicating traditional, face-to-face classroom practices.